Faster growth rate in ad libitum-fed cats: a risk factor predicting the likelihood of becoming overweight during adulthood - Serisier, Samuel (Cambridge University Press, 2013)
In human subjects, the risk of becoming overweight (OW) in adulthood is largely determined early in childhood. However, early-life factors have not been considered for feline obesity. A total of eighty colony cats, fed ad libitum, were studied; various breeds, ages and sex were included, with thirty-six (45 %) being OW and forty-four (55 %) being of ideal weight (IW). The effects of various factors (including age, sex, neuter status, breed (pure v. mixed), mean daily food intake (FI), housing status (indoor with outdoor access v. exclusively indoor) and body weight at 1 year of age (BW1y)) on weight status were assessed. Initial statistical analyses identified BW1y as the main significant variable. Body weight (BW) and FI were then assessed between 1 and 8·5 years of age, with group differences (OW v. IW) noted for BW, which increased significantly with age only in the OW group (P < 0·001). However, no difference in BW (P = 0·17) was noted when BW1y was included as a covariate in the model. FI did not change with age in either group. Finally, given the importance of BW1y, changes in BW from 3 to 12 months were then assessed with BW at 3 months of age included as a covariate. Whereas at 3 months of age, no group difference in BW was observed, a faster rate of weight gain was seen in OW cats. In conclusion, as in human subjects, the rate of growth is a key risk factor for cats becoming OW, although the factors responsible are currently not known.